Changing Attitudes Towards Research Through a Course-based Undergraduate Research Experience - Keith Brazendale; Michael Rovito; Jeanette Garcia (Journal of the Scholarship of Teaching and Learning)
Studies show undergraduate students typically view research-focused educational courses negatively, with students reporting feelings of anxiety, difficulty, detachment, and reduced perceptions of relevancy to their own life. Course-based undergraduate experiences (CUREs) can provide research-related experiences to a large number of students in a convenient fashion, thus, are well-positioned to shift student perceptions of research. The purpose of this study is to explore changes in attitudes towards research in a large sample of undergraduate students’ after completing one semester of a CURE. This study used a within-subjects pre-posttest design. Data collection took place over eight semesters from fall 2019 through spring 2022 at a large metropolitan public university in the southeast region of the United States. Students enrolled in the CURE were asked to complete the Attitude Towards Research scale at the beginning and end of the semester covering the following factors: usefulness of research (F1), anxiety (F2), affect indicating positive feelings about research (F3), life relevancy of research to the students’ daily lives (F4), and difficulty of research (F5). Wilcoxon signed rank tests for paired data were conducted and Mann-Whitney U tests assessed whether there were any differences between students who completed the course face-to-face versus online. Across all eight semesters, 1,003 students (74% female, 91% Seniors) provided valid pre-posttest data. Statistically significant improvements were observed across all semesters (online and face-to-face) for research anxiety, positive attitude towards research, research relevance to own life, and research difficulty from the ATR scale (p<0.05). For usefulness of research for profession (F1), statistically significant differences were observed in four out of the eight semesters (p<0.05). Changes in students’ attitudes towards research did not differ between course modality (face-to-face versus online) except for F1. The mean change in F1 was different between students taking a face-to-face (mean: 0.22, ±SD 1.02) versus online version (mean: 0.07, ±SD 0.72) of the course (z = 2.35, p = 0.02). Findings from this study demonstrate the potential of a CURE at reducing anxiety, lowering perceived difficulty, enhancing overall impressions, and students’ overall attitudes toward research and research-based education. Continued consideration and evaluation of how and what is delivered in CUREs to students is required to advance the pedagogy of research methods.